OR04-06 G Protein G(S)α in Muscle Is Essential for Survival During Cold Adaptation in the Absence of Thermogenesis of Brown Adipose Tissue - Chen, Min (J Endocr Soc, 2020)
Adaptive thermogenesis is important for the control of body temperature (Tb) and maintenance of body weight, and it is primarily regulated by sympathetically-driven brown adipose tissue (BAT). Studies indicate that muscle is also involved in thermogenic regulation. G(s)α couples to ligands and receptors, including β-adrenergic receptors, to increase intracellular cAMP. Our previous studies have showed that mice with adipose-specific G(s)α deficiency had inactive BAT and impaired cold tolerance. To determine whether G(s)α/cAMP signaling in skeletal muscle compensates for loss of BAT thermogenesis, we generated mice with G(s)α deficiency in adipocyte tissue alone (AdipGsKO), in skeletal muscle alone (SkMGsKO) or in both (AdipSkMGsKO). Compared to control mice, AdipGsKO and SkMGsKO mice had normal body weight, while AdipSkMGsKO showed reduced body weight with normal food intake and energy expenditure. Both AdipGsKO and AdipSkMGsKO mice had elevated fasting glucose levels, but similar glucose tolerance to control or SkMGsKO mice. SkMGsKO mice displayed reduced insulin sensitivity. When acutely exposed to 6(o)C for 3 hours, AdipGsKO and AdipSkMGsKO mice rapidly decreased their Tb, indicating that they are sensitive to acute cold exposure, consistent with their inactive BAT. To assess adaptation to chronic cold, mice were exposed to gradually declining ambient temperature from 22(o)C to 6(o)C with a daily decrease of 2(o)C and were then kept at 6(o)C for 5 days. As expected, both AdipGsKO and AdipSkMGsKO mice failed to stimulate BAT UCP1 by cold adaptation. Unexpectedly, AdipGsKO mice maintained normal Tb similar to control and SkMGsKO mice. However, AdipSkMGsKO mice started to rapidly drop their Tb when ambient temperature declined to 14(o)C and 85% of SkMGsKO mice (11/13) died before the end of experiment. These results suggest that when there is a lack of BAT function, G(s)α/cAMP signaling in muscle plays an essential role for mice to survive in response to chronic cold challenge.